Glutamate biosensor imaging reveals dysregulation of glutamatergic pathways in a model of developmental cortical malformation - Dulla, CG (2012)
Cortical malformations can cause intractable epilepsy, but the underlying epileptogenic mechanisms are poorly understood. We used high-speed glutamate biosensor imaging to ask how glutamatergic signaling is altered in cortical malformations induced by neonatal freeze-lesions (FL). In non-lesion neocortical slices from 2–8 week old rats, evoked glutamate signals were symmetrical in the medio-lateral axis and monotonic, correlating with simple, brief (≈ 50 ms) local field potentials (LFPs). By contrast, in FL cortex glutamate signals were prolonged, increased in amplitude, and polyphasic, which paralleled a prolongation of the LFP. Using glutamate biosensor imaging, we found that glutamate signals propagated throughout large areas of FL cortex and were asymmetric (skewed towards the lesion). Laminar analysis demonstrated a shift in the region of maximal glutamate release towards superficial layers in FL cortex. The ability to remove exogenous glutamate was increased within the FL itself but was decreased in immediately adjacent regions. There were corresponding alterations in astrocyte density, with an increase within the lesion and a decrease in deep cortical layers surrounding the lesion. These findings demonstrate both network connectivity and glutamate metabolism are altered in this cortical malformation model and suggests that the regional ability of astrocytes to remove released glutamate may be inversely related to local excitability.